Clinimetric properties of lower limb neurological impairment tests for children and young people with a neurological condition: A systematic review. - Ramona Clark; Melissa Locke; Bridget Hill; Cherie Wells; Andrea Bialocerkowski (PLoS ONE, 2017)
Background Clinicians and researchers require sound neurological tests to measure changes in neurological impairments necessary for clinical decision-making. Little evidence-based guidance exists for selecting and interpreting an appropriate, paediatric-specific lower limb neurological test aimed at the impairment level. Objective To determine the clinimetric evidence underpinning neurological impairment tests currently used in paediatric rehabilitation to evaluate muscle strength, tactile sensitivity, and deep tendon reflexes of the lower limb in children and young people with a neurological condition. Methods Thirteen databases were systematically searched in two phases, from the date of database inception to 16 February 2017. Lower limb neurological impairment tests were first identified which evaluated muscle strength, tactile sensitivity or deep tendon reflexes in children or young people under 18 years of age with a neurological condition. Papers containing clinimetric evidence of these tests were then identified. The methodological quality of each paper was critically appraised using standardised tools and clinimetric evidence synthesised for each test. Results Thirteen papers were identified, which provided clinimetric evidence on six neurological tests. Muscle strength tests had the greatest volume of clinimetric evidence, however this evidence focused on reliability. Studies were variable in quality with inconsistent results. Clinimetric evidence for tactile sensitivity impairment tests was conflicting and difficult to extrapolate. No clinimetric evidence was found for impairment tests of deep tendon reflexes. Conclusions Limited high-quality clinimetric evidence exists for lower limb neurological impairment tests in children and young people with a neurological condition. Results of currently used neurological tests, therefore, should be interpreted with caution. Robust clinimetric evidence on these tests is required for clinicians and researchers to effectively select and evaluate rehabilitation interventions.